2016
DOI: 10.4148/1944-3676.1113
|View full text |Cite
|
Sign up to set email alerts
|

Bare Nouns in Brazilian Portuguese: An experimental study on grinding

Abstract: Much literature has explored the interpretation of the bare singular (BS) in Brazilian Portuguese. Pires de Oliveira & Rothstein (2011) claim that BS nouns are mass because they denote kinds and argue that this explains why only the BS in Brazilian Portuguese can have a non-cardinal interpretation. In this paper, based on an experimental task with Brazilian Portuguese adult speakers, we explore one of their predictions, namely that the 'volume interpretation' of the BS cannot be explained as a case of Grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Other shifts in the count/mass domain include the universal grinder (Pelletier, ), where count nouns are interpreted as mass, as in “There is banana all over the road,” and the universal sorter (Bunt, ), which derives sorts from substances (Bunt, ). Much literature has explored different types of coercion since they were originally described, including experimental studies (see,e.g., Beviláqua, Lima, & Pires de Oliveira, ; Frisson & Frazier, ). Cf.…”
mentioning
confidence: 99%
“…Other shifts in the count/mass domain include the universal grinder (Pelletier, ), where count nouns are interpreted as mass, as in “There is banana all over the road,” and the universal sorter (Bunt, ), which derives sorts from substances (Bunt, ). Much literature has explored different types of coercion since they were originally described, including experimental studies (see,e.g., Beviláqua, Lima, & Pires de Oliveira, ; Frisson & Frazier, ). Cf.…”
mentioning
confidence: 99%
“…:Beviláqua and Pires de Oliveira ( 2014)). The issue is whether it is contextually dependent, as argued by Lima and Gomes (2016) and Beviláqua et al (2016) or not. The results indicate that besides a cardinal reading, the volume interpretation is significantly associated with the BS, independently of the context.…”
mentioning
confidence: 99%
“…Bale and Barner (2009)), then this contrast between the BS and the BP in BrP shows that the BS behaves massively. Beviláqua et al (2016) and Lima and Gomes (2016) also explored the possibility of the BS being compared by volume dimensions. Beviláqua et al's (2016) performed a Truth-Value Judgment Test (TVJT) and the results showed that the volume comparison is unlikely to be chosen when the cardinality comparison is available for BS nous (against Beviláqua and Pires de Oliveira's (2014) results).…”
mentioning
confidence: 99%
See 2 more Smart Citations